Puericulture consultation: problems found in those under 2 years old - Ferreira, Fabiana Angelo; Freitas, Rosideyse de Souza Cabral; Santos, Maria Carolina Salustino dos; Silva, Suélida Rafaela de Melo; Silva, Amanda Marinho da; Santos, Mirelly Kerflem da Silva (Revista de Enfermagem UFPE on line, 2019)
Objective: to identify the main problems presented in children under 2 years of age during the nursing consultation in childcare. Method: this is a quantitative, descriptive, retrospective study. The universe of the survey was composed of 166 medical records of children attended at the child care clinic. It was identified, of these, 84 charts of children attended from 2012 to 2016. The results were presented in figures form. Results: data were analyzed by descriptive statistics and of the 84 children studied, a total of 139 complaints registered by the nurse during the child care consultation. Conclusion: respiratory problems (40%) followed by dermatological (33%) and gastrointestinal (23%) were highlighted. It is pointed out, by the study, the need to create a protocol of consultation of childcare for nurses, strengthening the prevention and promotion to the health of the child accompanied. Descritores: Child; Nurses, Male; Child Care; Pediatrics; Inquiry; Monitoring. Resumo Objetivo: identificar os principais problemas apresentados nas crianças menores de 2 anos durante a consulta de enfermagem em puericultura. Método: trata-se de estudo quantitativo, descritivo, retrospectivo. Compôs-se o universo da pesquisa por 166 prontuários de crianças atendidas na consulta de puericultura. Identificou-se, desses, 84 prontuários de crianças atendidas de 2012 a 2016. Apresentaram-se os resultados em forma de figuras. Resultados: analisaram-se os dados por estatística descritiva e, das 84 crianças estudadas, houve um total de 139 queixas registradas pelo enfermeiro durante a consulta de puericultura. Conclusão: destacaram-se os problemas respiratórios (40%) seguidos de dermatológicos (33%) e gastrointestinais (23%). Aponta-se, pelo estudo, para a necessidade de criar um protocolo de consulta de puericultura para os enfermeiros, fortalecendo a prevenção e promoção à saúde da criança acompanhada. Descritores: Criança; Enfermeiro; Puericultura; Pediatria; Intervenção; Cuidado. Consulta. Acompanhamento. Resumen Objetivo: identificar los principales problemas presentados en niños menores de 2 años durante la consulta de enfermería en puericultura. Método: se trata de un estudio cuantitativo, descriptivo, retrospectivo. El universo de la investigación estaba compuesto por 166 registros médicos de niños atendidos en la clínica de cuidado infantil. Se identificó, de estos, 84 cuadros de niños atendidos entre 2012 y 2016. Los resultados se presentaron en forma de figuras. Resultados: se analizaron los datos mediante estadísticas descriptivas y de los 84 niños estudiados, hubo un total de 139 quejas registradas por el enfermero durante la consulta de puericultura. Conclusión: se resaltaron los problemas respiratorios (40%) seguidos de dermatológicos (33%) y gastrointestinales (23%). Se señala, según el estudio, la necesidad de crear un protocolo de consulta de puericultura para enfermeros, fortaleciendo la prevención y promoción a la salud del niño acompañado. Descritores: Niño; Enfermeros Hombres; Cuidado del Niño; Pediatría; Consulta; Monitoreo.